Journalism, 1908 birth of a profession - Winfield, Betty Houchin, 1939- (University of Missouri Press, 2008)
"A team of media scholars with personal ties to the University of Missouri's School of Journalism explore the state of news organizations in 1908, the year in which the first university-based school of journalism was founded, and illustrate the profound impact journalism education has had on the news media"--Provided by publisher.